The depth of catheter in chronic subdural haematoma: does it matter?. (12th May 2019) - Weng, Weiji; Li, Hongpeng; Zhao, Xiaochun; Yang, Chun; Wang, Shen; Hui, Jiyuan; Mao, Qing; Gao, Guoyi; Feng, Junfeng
ABSTRACT: Objective : To investigate the appropriate depth of drainage catheter in the patients with chronic subdural haematoma (CSDH). Methods : We retrospectively analysed the data of 190 patients with CSDH undergoing single parietal burr-hole evacuation and drainage. Results : According to the depth of catheter (DC), 190 patients were divided into three groups: shallow group (DC <4.3 cm), middle group (DC 4.3 5.4 cm) and deep group (DC > 5.4 cm). During postdischarge 6 months, two, six and nine patients had recurrences in shallow, middle and deep groups, respectively. The recurrence rate in shallow or middle group was significantly lower than that in deep group. No significant difference in preoperative haematoma volume (PHV) was observed in three groups. While the residual subdural space (RSS) in shallow group was significantly smaller than those in the other two groups. The duration of drainage in shallow, middle and deep groups increased successively, and the differences were statistically significant. The total drainage volume (TDV) in shallow group showed no significant difference when compared with the other two groups. Conclusion : The depth of catheter may affect the outcome of CSDH. Inserting drainage catheter shallowly might be a preferred choice in patients with CSDH undergoing burr-hole evacuation and drainage.